Inherent Oxygen‐ and Nitrogen‐Doped Porous Carbon Derived from Biomass of Tamarind Leaf for High‐Performance Supercapacitor Application. Issue 1 (17th November 2020) - Chakraborty, Rishika; Maji, Pradip K.; Verma, Chhavi; Kumar Nayak, Arpan; Shankar Singha, Shib; Pradhan, Mukul
Abstract : Herein, oxygen‐ and nitrogen‐doped porous carbon material using tamarind leaves via simple chemical activation and carbonization process are presented. Subsequently, the as‐obtained material has not only exhibited a 3D hierarchical honeycomb‐like framework but equally reveals a high specific surface area of 1212 m 2  g −1 . In favor of the synergistic relationship between the tailored pore architecture and surface enriched heteroatoms, the electrochemical performances are evaluated in a three‐electrode system and by constructing a symmetric solid‐state device. A specific capacitance of 370, 293, and 193 F g −1 at 1 A g −1 is achieved in a three‐electrode system using H2 SO4, Na2 SO4, and KOH electrolytes, respectively, with electrochemical double‐layer capacitor (EDLC) and pseudocapacitive contributions. Moreover, a high energy density of 36.96 Wh kg −1 at 1 A g −1 and a high power density of 4.49 kW kg −1 at 10 A g −1 are obtained from the assembled solid‐state device along with excellent capacitive retention of 93% after 5000 cycles. Abstract : A 3D honeycomb‐like porous carbon with self‐doped O/N‐heteroatoms is synthesized from biomass of tamarind leaves which delivers high capacitive energy storage performance.